Cravings : how I conquered food - Collins, Judy, 1939- (Nan A. Talese, 2017)
"A candid memoir by folk legend Judy Collins of her lifelong struggle with compulsive overeating and the spiritual solution that saved her. Since childhood, Judy Collins has been preoccupied, haunted, seduced, and taunted by food, a problem that nearly cost her her career and her life. For decades she thought her food issues were moral issues--lack of self-will, lack of discipline--and she worked hard at controlling what she thought of as her shameful inclinations, employing measures that led to serious health complications. Today she knows she was born with an addiction to sugar and grains, flour and wheat. The discovery of a solution to her problem prompted the desire to share what she has learned, which has brought her peace of mind, a clean food plan,years of maintaining the same weight, and a glow of joy and health. Alternating between chapters on her life and those of the many diet gurus she has come to know (from Lord Byron to Atkins, Jean Nidetch of Weight Watchers, and Andrew Weil), Cravings is the story of the mountains Collins has climbed and the monsters she has encountered on the path to recovery"--